Synthesis and characterization of novel phthalocyanines bearing quaternizable coumarin - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
The synthesis of novel metal-free and zinc phthalocyanines with four 3-[(2-diethylamino)ethyl]-7-oxo-4-methylcoumarin dye groups on the periphery were prepared by cyclotetramerization of a novel 3-[(2diethylamino)ethyl]-7-[(3,4-dicyanophenoxy)]-4-methylcoumarin. The novel chromogenic compounds were characterized by elemental analysis, H-1 NMR, C-13 NMR, MALDI-TOF, IR and UV-Vis spectral data. The electronic spectra exhibit bands of coumarin identity along with characteristic Q and B bands of the phthalocyanine (Pc) core. The IR spectra of all the Pcs showed three characteristic intense bands, at 1704 cm(-1) for the lactone carbonyl and two bands at 1489-1604 cm(-1) for the conjugated olefinic system. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Coumarin (2H-chromen-2-one); Fluorescence; Metal-free; Phthalocyanines; Zinc; ELECTROCHEMISTRY; DERIVATIVES